Pemanfaatan Canva Sebagai Inovasi Pembelajaran Digital Pada Implementasi Kurikulum Merdeka Di SMP Negeri 11 Bengkulu Tengah - Sari, Venny Novita; Mardiana, Yessi; Prahasti, Prahasti; Wassalam, Ockhy Jey Fhiter; Damayanti, Sayka (Universitas Dehasen Bengkulu, 2024)
The development of digital technology provides significant opportunities to improve the quality of learning in schools, particularly in supporting the implementation of the Merdeka Curriculum which emphasizes innovative and creative learning. One of the digital tools that can be utilized in the learning process is Canva. This community service activity aims to improve students' understanding and skills at SMP Negeri 11 Bengkulu Tengah in utilizing Canva as a digital learning medium. The method used in this activity includes preparation, implementation of socialization and training, and evaluation stages. The implementation was carried out through the delivery of materials on how to use Canva and direct practice in designing learning posters. The results show that students were able to understand the use of Canva as a digital learning medium and were capable of creating simple, creative, and informative poster designs. Therefore, the use of Canva can be considered an innovative digital learning tool that supports the implementation of the Merdeka Curriculum in schools.